Стратегічні спроможності управління безпекою дорожнього руху в Україні - Поліщук, Володимир (Видавництво Львівської політехніки, 2015)
In this article attention is accented on the important argument of management of travelling motion safety from positions of statistics of accident in Ukraine, accordance of normatively legal base, safety of transport vehicles and participants of travelling motion, first medical aid, guidance and co-ordination of actions, legislation, mechanisms of financing, monitoring of safety of motion, investigation of accident, research government of motion safety base.
Strategy opportunities of the road safety management in Ukraine